2019
DOI: 10.1093/epolic/eiz007
|View full text |Cite
|
Sign up to set email alerts
|

Uber happy? Work and well-being in the ‘Gig Economy’

Abstract: SUMMARY We study the rise of the so-called ‘gig economy’ through the lens of Uber and its drivers in the United Kingdom. Using administrative data from Uber and a new representative survey of London drivers, we explore their backgrounds, earnings, and subjective well-being. We find that the vast majority of Uber drivers are male immigrants, primarily drawn from the bottom half of the London income distribution. Most transitioned out of permanent part- or full-time jobs and about half of drivers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 37 publications
(32 reference statements)
7
123
1
8
Order By: Relevance
“…At the same time, a number of studies have documented higher job satisfaction among the self-employed in the US and Europe (Benz and Frey, 2008a;Clark and Senik, 2006;Hundley, 2001;Blanchflower et al, 2001;Blanchflower and Oswald, 1998). Recent studies have also found higher levels of life satisfaction and lower distress among Uber drivers, a small but salient subset of the solo self-employed (Apouey and Stabile, 2020;Berger et al, 2018). We find that this extends to the solo self-employed and to other measures of well-being.…”
Section: Uk Contextsupporting
confidence: 67%
“…At the same time, a number of studies have documented higher job satisfaction among the self-employed in the US and Europe (Benz and Frey, 2008a;Clark and Senik, 2006;Hundley, 2001;Blanchflower et al, 2001;Blanchflower and Oswald, 1998). Recent studies have also found higher levels of life satisfaction and lower distress among Uber drivers, a small but salient subset of the solo self-employed (Apouey and Stabile, 2020;Berger et al, 2018). We find that this extends to the solo self-employed and to other measures of well-being.…”
Section: Uk Contextsupporting
confidence: 67%
“…Overall, workers report being satisfied with their gig economy work (53%), mainly because of the independence and flexibility aspects of their job. Berger et al [6] explored mental health outcomes of Uber "driver-partners" in London. Their study revealed that Uber drivers reported both higher levels of life satisfaction and higher levels of anxiety than other workers.…”
Section: Introductionmentioning
confidence: 99%
“…That this freelancer identity is articulated in opposition to an employee or worker identity reduces the likelihood of these workers claiming the rights which they may be legally entitled to. Indeed when offered the hypothetical choice between flexibility and greater labour protections, Uber drivers overwhelmingly support the former over the latter (Hall and Krueger, ; Berger et al ., ). This has frequently been deployed by Uber in its attempts to avoid regulation, despite the fact that labour protections may, in practice, only have limited impact on worker controlled flexibility (Berg and Johnstone, ).…”
Section: Control In the Gig Economymentioning
confidence: 97%